The Bisphenols Found in the Ejaculate of Men Does Not Pass through the Testes - Michal Ješeta; Kateřina Franzová; Simona Machynová; Jiří Kalina; Jiří Kohoutek; Lenka Mekiňová; Igor Crha; Bartosz Kempisty; Marek Kašík; Jana Žáková; Pavel Ventruba; Jana Navrátilová (Toxics, 2022)
Exposure to bisphenols is related to negative effects on male reproduction. The bisphenols exposure is associated with several modes of action including negative impact on the blood–testis barrier (BTB) in testes or direct effect on spermatozoa. Bisphenols have been detected in human seminal plasma, but the possible mechanism of seminal transfer of bisphenols is not clear. Some authors consider the transfer through the blood–testis barrier to be crucial. Therefore, in this work, we compared normozoospermic men and men after vasectomy who have interrupted vas deferens and their ejaculate does not contain testicular products. We measured the concentration of bisphenol A (BPA), bisphenol S (BPS) and bisphenol F (BPF) in the urine and seminal plasma of these men using liquid chromatography tandem mass spectrometry (LC/MSMS). We found that the ratio of urinary and seminal plasma content of bisphenols did not differ in normozoospermic men or men after vasectomy. From the obtained data, it can be concluded that the pathways of transport of bisphenols into seminal plasma are not primarily through the testicular tissue, but this pathway is applied similarly to other routes of transmission by a corresponding ejaculate volume ratio. To a much greater extent than through testicular tissue, bisphenols enter the seminal plasma mainly as part of the secretions of the accessory glands.